Issues arising from the use of university ilectures: A case study of one Australian campus - Dobinson, Toni; Bogachenko, T. (Social Science Press, 2018)
Â© 2018 Social Science Press. Australian universities have moved towards greater reliance on technology as a learning tool. The use of podcasts or recorded lectures (sometimes called ilectures) is now common practice in both on-campus and online modes. Using a qualitative approach to data collection which included recorded interviews, an online survey of open-ended questions and the researcher's own reflections on using ilectures, this study investigated 1) the impact of ilectures on the teaching and learning practices of both academics and students 2) student attendance in recorded lectures and 3) the responses of lecturers and students to being recorded. Findings highlighted a mix of reactions to, and experiences with, the ilecture learning tool, underscoring the need for lecturers and students to receive guidance in its use and for those driving the use of this technology to be fully mindful of the impact such a tool can have on teaching and learning.